Estimasi Pendugaan Biomassa Hutan Sekunder dan Daerah Reklamasi Menggunakan Data Citra ALOS PALSAR - Harry Tetra Antono (Program Studi Statistika Unisba, 2013)
Forests has an important role in stabilize CO2 concentrations in the atmosphere as a source ofcarbon emissions and can absorb carbon and store. It is often called a carbon sink program . Todevelop this program, it needs carbon stock data stored in the form of biomass using an effectivetechnique and easy to use. This study aimed to estimate the carbon content in the area ofreclamation and secondary forest resulting from mining activities through biomass allometricequation. Biomass values obtained by non-destructive method of sampling and biomass values wereused to develop allometric equations using regression analysis between the biomass with a diameterof tree. The study case was located at mine concession of PT. Insani Bara Perkasa, at the border ofKutai Kertanegara and West Kutai Districts, East Kalimantan Province. The allometric biomassequations for the reclamation area: B = 0.1 x 0.41 x D2+0.62, and for secondary forests: B = 0.118 xD2,31. This biomass allometric equations can be used to predict carbon reserves stored in thesecondary forest vegetation. This study also analysed the carbon stored using remote sensing. Theanalytical result from the ALOS PALSAR images of study area PT Insani Bara Perkasa describes thatcarbon sink potential is 7,83 ton/ha in reclamation area and 9,19 ton/ha in secondary forest. Theestimation of carbon uptake in reclamation area of PT Insani Bara Perkasa is 8.701,205 ton/ha and247.836,444 ton/ha in secondary forest.Those data suggest that the reclamation activity in the studyarea gave a little contribution to the carbon sink program yet.